Surgical treatment of primary solitary fibrous tumors involving the pelvic ring - Wang, Yifei; Wei, Ran; Ji, Tao; Chen, Zhongyan; Guo, Wei (PloS one, 2018)
The surgical treatment of primary solitary fibrous tumors (SFT) involving the pelvic ring has not been reported previously. In this study, we aimed to evaluate the efficacy of surgical treatment for this disease. From 2009 to 2015, 13 patients underwent tumor resection at our hospital, with an average age of 49.5 years (27-68 years). Four patients underwent en bloc resection, and 9 patients underwent piecemeal resections. A Chi-square test was used to compare the postoperative recurrence rates between the en bloc resection and the piecemeal resection groups (p = 0.68), and no significant difference was found between the benign and malignant solitary fibrous tumor groups (p = 0.44). The 5-year survival rate of the patients in this study was 83.3%, and the 5-year progression-free survival rate was 63.5%. The progression-free survival rate was not significantly different between the en bloc resection and piecemeal resection groups (p = 0.97). Piecemeal resection can also achieve acceptable local control, particularly for patients with sacral tumors, as they may achieve even better postoperative function with sacral nerve preservation. Recurrence and metastasis occur relatively late in the course of this disease. Therefore, long-term follow-up is required.